ENTREPRENEURIAL LEADERSHIP UNTUK MENYONGSONG REVOLUSI INDUSTRI 4.0 - Wijaya, Andreas; Santoso, Kevin (Universitas Bunda Mulia, 2020)
The demand of labour scarcity problem had been surge while the availability of labour market outpacing the available job. The data from BPS (2020) shows people graduated from higher school had a largest contribution compared from the other. Looking at this situation Indonesia ministry of industry (Kemenperin) recall an action to give an outlook of Industrial Revolution as an opportunity to drive more entrepreneur in Indonesia. It believes, Indonesia have a prolific people to compete the other South East Asian Country. However, the novelty of COVID-19 pandemic hardly hit many sector business, some of business also furlough or even to rid off their employee. As a result, negative growth is unavoidable, in April- June accounted to decreased -5,32% at least to be compared economic performance in year-to-year period. In order to cope the foresee situation, this community services had an initiative to emerged entrepreneurial leadership in industrial revolution era for higher education student. The aim of this services are to creating a young entrepreneur in future. Furthermore, two communication seminar was held in online media via (google meet) in Monday, mei 4th 2020 at 11.00pm until 13.00 pm. As a result, a positive feedback given by the student and they suggested to recall again with the specific issue in entrepreneurship area.